Building on an old feature in langue d'Oïl: interrogatives in Vimeu Picard. Issue 2 (July 2019) - Auger, Julie; Villeneuve, Anne-José
ABSTRACT: Picard faces challenges in its quest for recognition, in part due to its perceived similarity with French. While scholars recognize that Picard and French phonology, morphology and lexicon differ considerably, some scholars maintain that Picard syntax differs little from French. Suspecting that such assessments are based on superficial comparisons, we test their validity by performing comparative variationist analyses of Picard and French morphosyntactic structures. This article focuses on interrogatives. We compare older and contemporary written data, as well as contemporary oral data, and show that Picard and French use their shared structures differently and that the Picard Yes/No interrogative system is complex but constrained by two linguistic factors: polarity and person. We report very different distributions of SV, inversion and interrogative – ti based on polarity and show that negative markers point and mie constrain the choice of interrogative structure. For affirmative interrogatives, we show that the distribution of interrogative structures is strongly constrained by the subject person. A diachronic analysis of text from nine authors from three generations reveals overall stability over time, with some signs of convergence toward French in the middle generation but a reversal to the older patterns in the youngest generation.